Prevalence and determinants of depression and/or anxiety among adults using Kenya Demographic and Health Survey of 2022: Multilevel logistic regression analysis - Mamaru Melkam; Setegn Fentahun; Girmaw Medfu Takelle; Gidey Rtbey; Fantahun Andualem; Girum Nakie; Gebresilassie Tadesse; Yilkal Abebaw Wassie (PLoS ONE, 2025)
Introduction Depression and/or anxiety can be persistent or recurrent significantly affecting a person’s capacity to manage daily life, job, and school. The burden of depression and anxiety is rising from time to time, with serious consequences for overall health. Depression and anxiety are crippling conditions that can impact individuals of the whole community. Despite the high prevalence of depression and/or anxiety few studies were conducted that show the diagnosis levels of depression and/or anxiety in the community, particularly in Kenya. Therefore, this study aims to determine the prevalence of depression and/or anxiety and their determinant factors among adults in Kenya using data sourced from the 2022 Kenya Demographic and Health Survey. Method The Kenya demographic and health survey of 2022 data were used for this secondary data analysis in 2024. The survey included age groups ranging from 15 to 49, with a total sample size of 16,901 participants. Multilevel analysis was used to determine the prevalence of depression and/or anxiety with determinant factors at the 95% CI. Results The overall prevalence of depression and/or anxiety was 3.84% with a 95% CI of (3.56, 4.14). Of this, 2.85% have only depression, 1.97% have only anxiety disorders, and 0.98% have comorbid depression and anxiety. In multivariable multilevel logistic regression analysis sexually violated, having a chronic medical illness, being divorced and widowed, having a job, and being HIV positive were associated with depression and/or anxiety with a p-value of less than 0.05. Conclusions According to the findings of this study the prevalence of depression and/or anxiety was 3.84%. This finding poses a significant challenge for the community to perform their daily tasks. As a result, the healthcare systems of Kenya have to mitigate the burden of depression and/or anxiety. All the clients must be treated since they received a diagnosis as reported by the physician.